Reprogramming the tumor microenvironment – macrophages emerge as key players in breast cancer immunotherapy - Sami, Ana; Raza, Afsheen (Frontiers in Immunology, 2024)
Breast cancer has the highest global incidence among all cancers, affecting more than 2 million individuals annually. Despite the availability of new drugs and novel treatment combinations, it is postulated that the incidence and mortality of breast cancer will rise by 40.8% and 51.9% respectively by 2040. Such dire statistics are associated with the clonal evolution of cancer cells that leads to therapeutic resistance and consequent relapse in breast cancer patients. On the other hand, the tumor microenvironment (TME) comprising of tumor cells, cancer-associated immune cells, re-programmed stromal cells, and the extracellular matrix (ECM) creates an immunosuppressive niche facilitating immune evasion. This review focuses on a critical cellular component of the tumor microenvironment, the tumor-associated macrophages (TAMs) in breast cancer immunotherapy. Macrophages are inherently plastic and can convert from an anti-tumor M1 phenotype to a pro-tumor M2 phenotype based on microenvironmental cues. Cancer cells facilitate these cues, allowing the tumor-associated macrophages to gain M2 phenotype and mediate immune evasion. Therefore, knowledge of the distinct role of tumor-associated macrophages in immune evasion can help design therapeutics such as engineered macrophages, M2 targeting drugs, and novel macrophage-mediated drug delivery strategies for long-term survival in breast cancer.